Metaphor-based approach to representing writing tasks - Stoner, Frank, author; Kiefer, Kathleen, advisor; Merolla, Andrew, committee member; Doe, Sue, committee member (Colorado State University. Libraries, 2010)
This document argues that the long-standing practice of imitation within the field of rhetoric, along with recent qualitative studies in rhetoric and composition, foster problematic attitudes of student deficiency. In this thesis, I propose a cognitive theory based alternative. Recent work in cognitive science, metaphor theory, and linguistics suggests that metaphors may be more significant than mere nourishes of style—they may be evidence of mental structures called schema that organize the human mind. 1 argue that certain generative metaphors can be drawn from students' own experiences to help them more successfully set goals, plan, and mentally represent writing tasks. This approach empowers students by focusing their attention on their own experiences rather than problematically requiring students to rely upon expert writing models.
Covers not scanned.
Keywords: English language -- Rhetoric -- Study and teaching; Metaphor